Effects of Soil-Transmitted Helminths and Intestinal Protozoan Infections on Haemoglobin Levels among School-Aged Children in Belo and Bui, North West Cameroon: A Cross-Sectional Study - Frederick Nchang Cho; Humphrey Ngala Ngala; Ranibell Tung Bongazi; Rogers Sanga Kinsam; Beltha Tahnteng Tata; Desmond Aji; Paulette Ngum Fru; Patrick Kofon Jokwi (Journal of Parasitology Research)
Introduction. Soil-transmitted helminths (STH) remain a public health problem worldwide especially in low-income countries. Soil-transmitted helminths are known to affect both growth and haemoglobin levels. In this study, we determine the prevalence of intestinal parasites and explored its association with anaemia in school-aged children (SAC). Methodology. A cross-sectional study was carried out amongst pupils selected from 18 primary schools in four communities of the North West Region. Stool samples were examined using direct wet mount and formol-ether concentration techniques, while finger prick was performed for the measurement of haemoglobin with a haemoglobinometer. Results. The results showed significant variation of STHs, intestinal protozoan prevalence, and anaemia between age, sex, and communities. The prevalence of Ascaris lumbricoides, Trichuris trichiura, and hookworms was 15.1%, 0.8%, and 2%, respectively, with an overall STH prevalence of 18.3% across the four communities. Soil-transmitted helminths were more prevalent in Mbessa (30.2%) in comparison to Nkor (26.7%), Djottin (17.5%), and Kumbo (9.6%) communities. The prevalence of Entamoeba histolytica/dispar was 25.4% and Giardia duodenalis (6.9%), with an overall intestinal protozoa prevalence of 31% across the four communities. The prevalence of anaemia in the study population was 23.1%. Conclusion. Soil-transmitted helminths, intestinal protozoan infections, and anaemia are prevalent in the study area. Anaemia was observed to be associated with STH, intestinal protozoa, and the communities under study. This study recommends continuous deworming and health education on personal sanitation and environmental sanitation.